2019
DOI: 10.1016/j.rse.2019.04.022
|View full text |Cite
|
Sign up to set email alerts
|

A carbon sink-driven approach to estimate gross primary production from microwave satellite observations

Abstract: Global estimation of Gross Primary Production (GPP) -the uptake of atmospheric carbon dioxide by plants through photosynthesis -is commonly based on optical satellite remote sensing data. This presents a source-driven

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
50
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(51 citation statements)
references
References 98 publications
1
50
0
Order By: Relevance
“…These results depend on the frequency, sensor type (active or passive) and land cover [170]. In another study, it was found that GPP can be expressed as a function of VOD through a differential equation [171].…”
Section: Vod and Carbon Balancementioning
confidence: 96%
“…These results depend on the frequency, sensor type (active or passive) and land cover [170]. In another study, it was found that GPP can be expressed as a function of VOD through a differential equation [171].…”
Section: Vod and Carbon Balancementioning
confidence: 96%
“…Although VOD has often been used as a proxy of aboveground biomass (e.g. Liu et al, 2015;Tian et al, 2017;Brandt et al, 2018;Teubner et al, 2019), it is in fact determined by both biomass and plant water status (Konings et al, 2019). VOD variations within a day Li et al, 2017;Anderegg et al, 2018) and during soil dry-downs (Feldman et al, 2018;Zhang et al, 2019;Feldman et al, 2020) highlight the sensitivity of VOD to relative water content.…”
Section: Contribution Of Vod To Informing Plant Hydraulic Behaviormentioning
confidence: 99%
“…Droughts can have wide environmental and socio-economic impacts, ranging from their effects on climate, the carbon cycle, and food security to water availability. Droughts are typically induced by a lack of precipitation and/or an aboveaverage atmospheric demand for evapotranspiration (ET), which leads to an associated reduced availability of soil moisture in the root zone (Seneviratne et al, 2010;Teuling, 2018). The former is typically referred to as meteorological drought, whereas the latter is referred to as agricultural drought.…”
Section: Introductionmentioning
confidence: 99%